Associations between demographic characteristics and unmet supportive care needs in adults with cystic fibrosis. Issue Volume 12:Issue e2(2022) (31st August 2019) - Obregon, Laura Liliana; Jeong, Kwonho; Hoydich, Zachariah P; Yabes, Jonathan; Pilewski, Joseph; Richless, Connie; Moreines, Laura T; Dellon, Elisabeth P; Goss, Christopher H; Arnold, Robert M; Kavalieratos, Dio
Abstract : Context: Patients living with cystic fibrosis (CF) report impaired quality of life. Little is known about unmet supportive care needs among adults living with CF and how they are associated with demographic characteristics. Objectives: The primary objective of this study was to identify associations between demographic variables and unmet supportive care needs regarding anxiety, sadness, pain and uncertainty about the future of living with CF. Methods: We recruited 165 adults with CF from a single academic medical centre to complete a brief demographic survey and the Supportive Care Needs Survey (SCNS-34), a validated self-reported needs assessment that measures the prevalence of and preferences for support for 34 needs that commonly occur in patients with serious illness. Results: Approximately half of the participant sample was male, with a median age of 29 years, varying income levels and a range of lung disease severity. We found statistically significant associations between insufficient income and increased odds of reporting need for support regarding anxiety (OR: 6.48; 95% CI 2.08 to 20.2), sadness (OR: 6.15; 95% CI 2.04 to 18.5), pain (OR: 7.06; 95% CI 2.22 to 22.4) and worries surrounding uncertainty about the future (OR: 3.43; 95% CI 1.18 to 9.99). Conclusion: Adults with CF report significant unmet needs for support in several physical and emotional domains. Many of these domains were associated with demographic characteristics, most notably, income. Our findings underscore the importance of developing treatment approaches that are sensitive to patient demographics when addressing unmet supportive care needs among adults with CF.